Protective effects of mitochondria‐targeted antioxidants and statins on cholesterolinduced osteoarthritis. Issue 1 (13th October 2016) - Farnaghi, Saba; Prasadam, Indira; Cai, Guangping; Friis, Thor; Du, Zhibin; Crawford, Ross; Mao, Xinzhan; Xiao, Yin
Abstract : The contribution of metabolic factors on the severity of osteoarthritis (OA) is not fully appreciated. This study aimed to define the effects of hyper cholesterolemia on the progression of OA. A polipoprotein E‐deficient (ApoE −/− ) mice and rats with diet‐induced hypercholesterolemia (DIHC) rats were used to explore the effects of hyper cholesterolemia on the progression of OA. Both models exhibited OA‐like changes, characterized primarily by a loss of proteoglycans, collagen and aggrecan degradation, osteophyte formation, changes to subchondral bone architecture, and cartilage degradation. Surgical destabilization of the knees resulted in a dramatic increase of degradative OA symptoms in animals fed a high‐cholesterol diet compared with controls. Clinically relevant doses of free cholesterol resulted in mitochondrial dysfunction, overproduction of reactive oxygen species (ROS), and increased expression of degenerative and hypertrophic markers in chondrocytes and breakdown of the cartilage matrix. We showed that the severity of diet‐induced OA changes could be attenuated by treatment with both atorvastatin and a mitochondrial targeting antioxidant. The protective effects of the mitochondrial targeting antioxidant were associated with suppression of oxidative damage to chondrocytes and restoration of extracellular matrix homeostasis of the articular chondrocytes. In summary, our data show that hypercholesterolemia precipitates OA progression by mitochondrial dysfunction in chondrocytes, in part by increasing ROS production and apoptosis. By addressing the mitochondrial dysfunction using antioxidants, we were able attenuate the OA progression in our animal models. This approach may form the basis for novel treatment options for this OA risk group in humans.—Farnaghi, S., Prasadam, I., Cai, G., Friis, T., Du, Z., Crawford, R., Mao, X., Xiao, Y. Protective effects of mitochondria‐targeted antioxidants and statins on cholesterolinduced osteoarthritis. FASEB J. 31, 356–367 (2017) www.fasebj.org